On the “subjective reality” of Teodor Shanin’s peasant projects: Field studies, ‘long table’ method, and Peredelkino (an oral history approach) - Ilya Presnyakov (Крестьяноведение)
The article reconstructs the researchers’ “subjective reality” in Teodor Shanin’s peasant studies projects. While there has been extensive research on methodological, epistemological and empirical dimensions of these projects, little attention has been paid to personal experiences, emotions and transformations of the researchers. This study aims at filling this gap by reconstructing their subjective perceptions through oral histories, memories and published sources and also at ‘localizing’ such a subjective reality by examining its connection with the Peredelkino House of Creativity, where Shanin’s research team used to meet periodically. The article consists of the following parts: first, it outlines the broader conditions of Shanin’s peasant studies expeditions; then it focuses on “subjective reality of the first encounters” with Shanin and his ideas; the fieldwork is examined through the researchers’ observation of rural communities, their efforts to gain peasants’ trust and methodological challenges they faced; further, the study considers the long table discussions at Peredelkino, emphasizing their dual function as spaces for methodological and personal support; finally, the author explains institutionalization of the projects’ subjective reality through their lasting impact on research and educational initiatives of its participants. The findings show that the scholars’ subjective reality was deeply intertwined with the broader intellectual and social-political transformations of the 1990s, which resulted in the specific research culture of Shanin’s peasant studies projects — a combination of reflections on ethnographic experiences, analytical and methodological frameworks with personal experiences, friendship, and intellectual partnership.